2016
DOI: 10.2147/cia.s96017
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein intake in sarcopenic obese older women

Abstract: ObjectiveTo determine the prevalence of sarcopenia in a population of obese older women and to assess the effect of a diet moderately rich in proteins on lean mass in sarcopenic obese older women.Materials and methodsA total of 1,030 females, >65 years old, body mass index >30 kg/m2, were investigated about their nutritional status. Muscle mass (MM) was estimated according to the Janssen equation (MM =0.401× height2/resistance measured at 50 kHz +3.825× sex −0.071× age +5.102). Sarcopenia was defined according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 43 publications
4
72
0
3
Order By: Relevance
“…Only 28 (43%) of our patients with depression and 44 (68%) of the control group obtained more than 15% of their energy from protein sources. A consequence of inadequate protein intake is a negative nitrogen balance and the decline of protein levels, especially that of skeletal muscle proteins 31. In our study, a higher percentage protein intake was associated with better functional and cognitive status.…”
Section: Discussionsupporting
confidence: 55%
“…Only 28 (43%) of our patients with depression and 44 (68%) of the control group obtained more than 15% of their energy from protein sources. A consequence of inadequate protein intake is a negative nitrogen balance and the decline of protein levels, especially that of skeletal muscle proteins 31. In our study, a higher percentage protein intake was associated with better functional and cognitive status.…”
Section: Discussionsupporting
confidence: 55%
“…A previous study has reported that protein intake can prevent muscle mass loss associated with weight loss in obese older women 25. Another study reports that using gelatin as a single diet protein results in appetite suppression in adults, which is more significant than using casein 26.…”
Section: Discussionmentioning
confidence: 99%
“…[38], na podstawie oceny zależności pomiędzy fenotypem metabolicznie zdrowych otyłych starszych (metabolically healthy obese -MHO) -5314 osób w średnim wieku 68 lat -a wystąpieniem ryzyka chorób sercowo-naczyniowych, wskazują, że występowanie otyłości u badanych (bez zespołu metabolicznego) nie zwiększa ryzyka chorób układu sercowo-fat mass is accompanied by decreased muscle mass, while obesity masks muscle mass deficiency and undernutrition [35]. The incidence of sarcopenic obesity increases with age irrespective of gender, from 13.5% in men under 70 to 17.5% in men over 80, and from 5.3% in women under 70 to 8.4% in women over 80 [41], resulting in an increased risk of impaired mobility and disability, as well as increased morbidity and overall mortality. Baumgartner et al define sarcopenic obesity as a value of the relative muscle mass index (muscle mass against square height).…”
Section: Redukcja Masy Ciała Jako Zalecenie Leczniczeunclassified